Riko The Series: Instilling Honest Character in Early Childhood Through Animated Film - Imara, Faridah Ummu; Turhan Yani, Muhammad; SyaÔÇÖdullah, Achmad (Journal of Islamic Education Students (JIES), 2024)
Character education in early childhood, especially the value of honesty, is an important aspect in forming a positive personality. This article explores the use of the animated film "Riko The Series" as a learning medium for developing honest characters in early childhood. The method used in this research is qualitative with a descriptive approach. Primary data was obtained from analysis of dialogue in films, while secondary data was obtained from previous research. The analysis results show that this film conveys a moral message, especially the value of honesty, through interactions between characters. This film depicts the daily life of a child who is religious, independent and honest. Specific episodes from season 4 of Riko The Series show a strong emphasis on honesty and responsibility. In conclusion, the animated film "Riko The Series" has great potential as a supporting tool in forming honest characters in early childhood.┬á┬á